Ruin Beach (DI Ben Kitto #2) - Kate Rhodes (London Simon & Schuster, 2019)
DI Ben Kitto has become the Scilly Islands' Deputy Chief of Police. As the island's lazy summer takes hold, he finds himself missing the excitement of the murder squad in London. But when a body is found anchored to the rocks of a nearby cave, it appears he's spoken too soon. The island of Tresco, and the deep and murky waters that surround it, hold a dark secret. One that someone seems desperate to uncover . . .
Keywords: Fiction; Crime; Mystery; Thriller